2015
DOI: 10.1016/j.nano.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of singlet oxygen generated by a broad-spectrum viral fusion inhibitor on membrane nanoarchitecture

Abstract: Targeting membranes of enveloped viruses represents an exciting new paradigm to explore on the development of broad-spectrum antivirals. Recently, broad-spectrum small-molecule antiviral drug were described, preventing enveloped virus entry at an intermediate step, after virus binding but before virus–cell fusion. Those compounds, including an oxazolidine-2,4-dithione named JL103 that presented the most promissing results, act deleteriously on the virus envelope but not at the cell membrane level. In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…The results from the PIV5 infection system, taken together with the results from the HeV F cellular experiments, highlight the critical nature of fusion protein TM-TM interactions for maintenance of viral infectivity and demonstrate a potential for smallmolecule inhibitors that disrupt TM-TM interactions or modulators of lipid environment to serve as antiviral candidates. A study with paramyxoviruses found that a broad-spectrum small-molecule drug (JL103) could prevent membrane fusion by altering lipid architecture (37). Changes in the lipid environment caused by small-molecule inhibitors may be able to alter fusion protein TM-TM interactions and therefore disrupt fusion protein function.…”
Section: Discussionmentioning
confidence: 99%
“…The results from the PIV5 infection system, taken together with the results from the HeV F cellular experiments, highlight the critical nature of fusion protein TM-TM interactions for maintenance of viral infectivity and demonstrate a potential for smallmolecule inhibitors that disrupt TM-TM interactions or modulators of lipid environment to serve as antiviral candidates. A study with paramyxoviruses found that a broad-spectrum small-molecule drug (JL103) could prevent membrane fusion by altering lipid architecture (37). Changes in the lipid environment caused by small-molecule inhibitors may be able to alter fusion protein TM-TM interactions and therefore disrupt fusion protein function.…”
Section: Discussionmentioning
confidence: 99%
“…Novel lipophilic thiazolidine derivatives, such as LJ001 and JL103, are membrane-binding photosensitizers that produce singlet oxygen molecules to induce changes in the properties of lipid membranes and prevent fusion between viral and target cell membranes. They exhibit broad-spectrum activities against numerous enveloped viruses and may be active against CoVs [184][185][186][187] .…”
Section: Viral Envelope Membrane Nucleocapsid and Accessory Proteinmentioning
confidence: 99%
“…13), are membrane-binding photosensitizers that produce singlet oxygen molecules to induce changes in the properties of lipid membranes and prevent fusion between viral and target cell membranes. They exhibit broad-spectrum activities against numerous enveloped viruses and may be active against CoVs [164][165][166][167]. In addition to the above-mentioned molecules, there are numerous peptide-based inhibitors of coronaviruses [168].…”
Section: Figure 13mentioning
confidence: 99%